Global and regional factors responsible for the drowning of the Central Apennine Chattian carbonate platforms. (2nd June 2014) - Brandano, Marco; Lustrino, Michele; Cornacchia, Irene; Sprovieri, Mario
<x xml:space="preserve">Abstract</x> This work discusses and interprets the factors responsible for the Oligocene–Miocene drowning of the Central Apennine platform deposits, based on facies and stable‐isotope analyses of two representative stratigraphic sections. The Mediterranean carbonate platforms were affected during the Oligocene–Miocene boundary by a carbonate production crisis that was induced by global factors and amplified by regional events, such as volcanic activity. The positive δ13C shift observed in the studied sections corresponds to vertical facies changes reflecting the evolution from middle carbonate ramp to outer ramp‐hemipelagic depositional environments. This drowning event is recorded not only in the Apennine platforms, but also in other Mediterranean platforms such as in southern Apulia, Sicily and Malta, and outside the Mediterranean Basin. The 24–23.5 Ma Mi‐1 glacial maximum may have had a significant influence on this drowning event because it was associated with high rates of accumulation of continent‐derived sediments. The increased continental weathering and runoff sustained high trophic conditions. These probably were a consequence of the Aquitanian–Burdigalian volcanic activity in the Central‐Western Mediterranean, that may have led to an increase in nutrient content in seawater and an increase in atmospheric and marine CO2 concentrations. Copyright © 2014 John Wiley & Sons, Ltd.